Direct and indirect antimicrobial effects of α-mangostin on pathogenic microorganisms - Syed Ibrahim, Nurul Huda; Bakhtiar, M. Taher; Darnis, Deny Susanti; Mohamed Amiroudine, Mohamed Zaffar Ali; Ahmed, Qamar Uddin (Coastal Life Medicine Media co., Limited, 2014)
Objective: To test direct and indirect antimicrobial properties of α-mangostin towards a number of bacteria and fungi. Methods: The experiment was carried out using broth microdilution and checkerboards methods. Activity of α-mangostin paired with an antibiotic was studied by calculating its fractional inhibitory concentration (FIC). Results: The activity of all four bacteria towards ampicillin, penicillin G, streptomycin and tetracycline showed no interaction with the combination with α-mangostin where the FIC indexes were between the range of 0.5<FICindex>4. Activity of doxycycline on Pseudomonas aeruginosa fell into other set of range, FICindex≥4 which is an antagonism. Conclusions: The FIC index is far away in the range. The coupled antibiotic and α-mangostin is considered synergy in action if it lies in FICindex≤0.5 and it was found that the isolated compound, α-mangostin revealed very low synergistic antimicrobial effects when coupled with antibiotics.